Student Social Conflicts with Teacher and Its Handling on Guidance and Counseling - Aldi Ihsandi; Amirah Diniaty (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Qualitative approach was used in this research and it was in the term of the type of data. The qualitative approach type was a research producing qualitative descriptive data, an approach produced data in the forms of written or spoken words of people and behaviors that could be observed. This research aimed at knowing the causes of student social conflicts with teachers at State Junior High School 1 Bandar Laksamana, Bengkalis Regency, Riau and its handling by a Guidance and Counseling teacher. The subjects of this research were the students, and the objects were student social conflicts with teachers and its handling on Guidance and at State Junior High School 1 Bandar Laksamana, Bengkalis Regency, Riau. The main informants were 9 persons. The informants were 4 students having social conflicts with teachers, 4 teachers having social conflicts with students, and a Guidance and Counseling teacher. Interview and documentation were the techniques of collecting the data. The research findings showed that the causes of student social conflicts with teachers at State Junior High School 1 Bandar Laksamana, Bengkalis Regency, Riau were (1) communication, (2) coming late to the class, (3) not doing the assignment, (4) truanting or not joining the learning, (5) smoking, and (6) dissent. Its handling by a Guidance and Counseling teacher was (1) giving advice, (2) giving punishment, (3) giving a service in Guidance and Counseling, (4) the role of parents, and (5) the handling by the headmaster.